Proportion and associated factors of glaucoma among outpatient department at university of Gondar comprehensive specialized hospital tertiary eye care and training center, northwest Ethiopia, 2021 - Yekunoamelak, Banchamelak Zeraye; Ayele, Fisseha Admassu; Bogale, Zinachew Mulat; Worku, Endalew Mulugeta (Frontiers in Ophthalmology, 2025)
PurposeThe purpose of this study is to measure the proportion, types of glaucoma, and associated factors among outpatient departments at the University of Gondar Comprehensive Specialized Hospital Tertiary Eye Care and Training Center, Northwest Ethiopia.MethodsAn institution-based cross-sectional study design was conducted on 934 participants who were selected by a simple random sampling method at entrance of tertiary eye care and training Center from September to November 2021. A structured questionnaire was used to collect the data through interviews, and the presence or absence, type, and stage of glaucoma were determined by reviewing the chart. The questionnaire was adapted from a previous study, and the data were entered into Epi Info version 7 and analyzed using SPSS version 20. Descriptive data were analyzed in terms of proportion, frequency, mean, and standard deviation. Binary logistic regression was utilized to identify determinant factors, with significance considered at a p-value less than 0.05.ResultsA total of 934 study participants with an 85.33% response rate took part in the study. The mean age of the study participants was 55.67 SD ± 13.21 years. The proportion of glaucoma was 13.4% [(95% CI: (10.9, 15.8)], with Primary Open Angle glaucoma accounting for 96.3% of the total number of glaucoma cases. The age groups of 56-66 [AOR=3.80(95% CI: 1.99-7.26)], 67-87 [AOR=5.34(95% CI: 2.70-10.45)] and those who completed college or university [(AOR= 5.41(95% CI: 2.12-13.82)] were significantly associated with the presence of glaucoma.ConclusionThis study shows a high proportion of glaucoma compared to other studies, with Primary Open Angle Glaucoma being the most prevalent type. Increasing age and higher education level were significantly linked to the presence of glaucoma. Further research is needed to explore the relationship between education level and glaucoma.